Antibacterial Potential of Red Betel Leaf (Piper crocatum) Extract for Women’s Reproductive Health - Pakpahan, Amkani Angelita; Bazura, Hughes; Susanto, Rafli; Hutabarat, Theresia Saurina Febriadella; Manda, Yutha N; Pratiwi, Nanda (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study looks at how red betel (Piper crocatum) extract can help keep women's reproductive health in good condition using natural methods. The research used a descriptive qualitative approach, mainly by looking at existing scientific articles and data from journals and databases between 2015 and 2025. The focus was on finding out which active ingredients are in red betel, how they fight bacteria, and why they might be useful in preventing infections in the female reproductive system. The research shows that red betel has compounds like flavonoids, alkaloids, tannins, and phenolics that work together to stop harmful bacteria from growing, especially Staphylococcus aureus and Pseudomonas aeruginosa. These compounds fight bacteria in several ways, such as breaking down the bacterial cell walls, stopping important enzymes from working, and messing up the bacteria's energy processes. Studies also show that using red betel in the form of a decoction can help reduce symptoms like vaginal discharge while keeping the good bacteria in the vagina balanced. Compared to man-made antiseptics, red betel has similar antibacterial effects but causes less irritation and is less likely to lead to bacteria becoming resistant. This makes it a promising option for a safe and eco-friendly natural alternative in feminine hygiene and women's health care. More research is needed to find the best way to extract these compounds and to test their effectiveness through proper clinical studies.